2021
DOI: 10.1101/2021.04.20.21255830
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Miami-Dade: A Case Study of Domestic Violence Arrests During the COVID-19 Pandemic

Abstract: The global health crisis that started early in 2020 has triggered a surge of interest in the effect (if any) of COVID-19 on patterns of domestic violence.1 The first systematic review and meta-analysis examining domestic violence during the pandemic revealed quite a lot of diversity in the approaches used to measure potential effects. Drawing on the time series forecasting literature, this brief report contributes to the growing body of evidence around the issue of domestic violence during the pandemic. Arrest… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
(5 reference statements)
1
5
0
Order By: Relevance
“…A series of additional conditional interpolation algorithms were developed and used to account for counties that failed to report on a given weekend day and then had artificially inflated counts when next reported (references provide additional information on the interpolation method used). 8,9…”
Section: Covid-19 Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of additional conditional interpolation algorithms were developed and used to account for counties that failed to report on a given weekend day and then had artificially inflated counts when next reported (references provide additional information on the interpolation method used). 8,9…”
Section: Covid-19 Casesmentioning
confidence: 99%
“…A novel, conditional interpolation method was developed and applied to handle erroneously deflated daily cases on holidays and inflated daily counts the day following a holiday (commonly referred to as “data dumps”), which occur in some counties but not others, and could lead to false-positive outliers being flagged. A series of additional conditional interpolation algorithms were developed and used to account for counties that failed to report on a given weekend day and then had artificially inflated counts when next reported (references provide additional information on the interpolation method used) …”
Section: Introductionmentioning
confidence: 99%
“…Hayyung Hospital Outpatient Hospital Selayar Islands Regency. The results of this study are in line with Mulyana et al (2021), stating that outpatient management must be based on the belief that good medical practice must be seen in health facilities. Those are derived from the design and flow, cleanliness, layout, comfort, location, and flow of patients.…”
Section: The Effect Of Facilities On Patient Waiting Timesupporting
confidence: 85%
“…This is supported by previous research conducted by Sam et al (2021) concluded that there is a positive and significant influence on the quality of human resources on work creativity. Creativity deals with thinking, finding new opinions and methods, and innovation in their use (Cahaya et al, 2022;Mulyana et al, 2021;Mustafa et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, policy efforts at the city, county, state and federal levels must protect immigrants of all documentation statuses and especially those with temporary and no protections who may fear that accessing critical resources will count against them under “public charge” (Fox, 2020). Indeed, Immigration and Customs Enforcement continued deporting immigrants during COVID‐19, separating families and disrupting financial stability during a global pandemic (Jordan, 2020). In an effort to support and expand communal health, protections for immigrants must be in place.…”
Section: Discussionmentioning
confidence: 99%